2011
DOI: 10.2174/1874396x01105010048
|View full text |Cite
|
Sign up to set email alerts
|

GE Models and Algorithms for Condensed Phase Equilibrium Data Regression in Ternary Systems: Limitations and Proposals

Abstract: Phase equilibrium data regression is an unavoidable task necessary to obtain the appropriate values for any model to be used in separation equipment design for chemical process simulation and optimization. The accuracy of this process depends on different factors such as the experimental data quality, the selected model and the calculation algorithm. The present paper summarizes the results and conclusions achieved in our research on the capabilities and limitations of the existing G E models and about strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Regarding practical and engineered oriented results, it is important to emphasize that better results are not always accomplished with the apparently superior models, as we showed [23] …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 78%
“…Regarding practical and engineered oriented results, it is important to emphasize that better results are not always accomplished with the apparently superior models, as we showed [23] …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 78%
“…Considering that Equation (1) is the dominant regression technique, it is expected and indeed found that many reported ternary parameters are thermodynamically inconsistent [4]. This is because, as discussed earlier, Equation (1) is only a necessary condition, which does not ensure that the solution is a global minimum.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Since there are numerous compositions that are able to satisfy the iso-activity criterion with a small residual, inconsistent solutions are often obtained [4]. Thus, the iso-activity criterion must be enforced with an absolute residual of at most 10 −4 to obtain a consistent solution.…”
Section: Thermodynamic Requirementsmentioning
confidence: 99%
“…The suitability of the surfactant as solvent for lactic acid extraction can be initially assessed by the type of the ternary system. The results indicated that all the systems studied belong to the Type 1 Treybal classification of ternary systems [35], with the water-surfactant binary pair exhibiting partial immiscibility. It is important to note that all the surfactants used in this study are mixtures containing different lengths of the alcohol component.…”
Section: Qualitative Liquid-liquid Equilibriamentioning
confidence: 94%